Effect of source temperature on the morphology and photoluminescence properties of ZnO nanostructures - Al-Azri, K.; Nor, R.M.; Amin, Y.M.; Al-Ruqeishi, M.S. (2010)
ZnO nanostructures have been synthesized by heating a mixture of ZnO/graphite powders using the thermal evaporation and vapor transport on Si(1 0 0) substrates without any catalyst and at atmospheric argon pressure. The in. uence of the source temperature on the morphology and luminescence properties of ZnO nanostructures has been investigated. ZnO nanowires, nanoflowres and nanotetrapods have been formed upon the Si(1 0 0) substrates at different source temperatures ranging from 1100 to 1200 degrees C. Room temperature photoluminescence (PL) spectra showed increase green emission intensity as the source temperature was decreased and ZnO nanowires had the strongest intensity of UV emission compared with other nanostructures. In addition, the growth mechanism of the ZnO nanostructures is discussed based on the reaction conditions. (C) 2010 Elsevier B. V. All rights reserved.